2005
DOI: 10.1016/j.ejcts.2004.12.059
|View full text |Cite
|
Sign up to set email alerts
|

Composite aortic root replacement in acute type A dissection: time to rethink the indications?

Abstract: A strategy of replacement rather than repair of the dissected aortic root for specific indications in type A dissection yielded high survival and low proximal reoperation rates. These results support an aggressive policy of composite root replacement in acute type A dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
67
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 19 publications
5
67
0
3
Order By: Relevance
“…Operative mortality was 12.3% in each group, and the ten year survival was 65% in the ARR group and 55% in the CRR group (P=0.48). There was a trend towards a higher incidence of root reoperation in the repair group (CRR n=4 vs. ARR n=0; P=0.08) (18). The Hannover group reported similar results in their series of 295 patients with TAAD.…”
Section: Aortic Root Replacement (Arr)supporting
confidence: 66%
See 1 more Smart Citation
“…Operative mortality was 12.3% in each group, and the ten year survival was 65% in the ARR group and 55% in the CRR group (P=0.48). There was a trend towards a higher incidence of root reoperation in the repair group (CRR n=4 vs. ARR n=0; P=0.08) (18). The Hannover group reported similar results in their series of 295 patients with TAAD.…”
Section: Aortic Root Replacement (Arr)supporting
confidence: 66%
“…Despite the increased risk associated with ARR, several large series comparing CRR to ARR have demonstrated equivalent operative mortality with a lower incidence of aortic root reoperation following ARR (8,18,19). The Mount Sinai group reviewed their experience with CRR compared to ARR in 162 patients with TAAD.…”
Section: Aortic Root Replacement (Arr)mentioning
confidence: 99%
“…This aggressive approach to the root was later advocated by Kouchoukos et (72,75), and it has since been revived again by Griepp's group at Mt. Sinai (76). The earlier practice at Stanford may have been overly conservative by saving the valve and sinuses in the vast majority of patients, but it appears to be the predominant treatment method in Japan where only 6.2% of AcA-AoD patients underwent root replacement in 2011 (77).…”
Section: Replacement Of the Valve And Rootmentioning
confidence: 99%
“…In the hands of expert thoracic aortic surgeons, the mortality risk may not be substantially elevated (76,78,80); however, the apparent safety of CVG root replacement may be due in part to publication bias as low risk has not been universally observed even among experienced surgeons (61,81). It is important to recall that the median number of proximal aortic operations among institutions performing at least one aortic operation per year in the Society of Thoracic Surgeons (STS) Adult Cardiac Surgery Database (ACSD) is only 12 per year per center (82).…”
Section: Replacement Of the Valve And Rootmentioning
confidence: 99%
“…Previous extensive studies demonstrated the safety of root replacement at the time of AD when the root tissue was involved (5,6). Since these patients tend to be younger, they have the most benefit to gain from preserving the native aortic valve when possible at the time of Type A repair and root replacement.…”
mentioning
confidence: 99%